Pendekatan Manajemen Perubahan untuk Mengoptimalkan Kinerja Sumber Daya Manusia di D’sruput, Lubuk Begalung, Padang - Jihan Atifa; Selvi Meiliani Saputri; Tri Yoma Elsa; Yuliana Fransiska; Ramdani Bayu Putra (Jurnal Visi Manajemen, 2025)
This trendy drink is very popular among young people. Competition between beverage shops can be seen from the emergence of various beverage shops that have distinctive characteristics. Direct observation of D'sruput MSME operations provides insight into production processes, inventory management, marketing strategies, and interactions with customers. Based on the results of interviews and field observations, several factors were found that trigger buying interest among young people, namely a comfortable place, friendly service, good taste and other factors. The many variations and unique restaurant names and menu names make it attractive to buy. Apart from that, the price is quite affordable and the packaging design is creative and attractive. Apart from that, research also finds that personal, social and psychological factors factor into young people's interest in buying trendy drinks. Therefore, it is hoped that this research will be useful for business people in the culinary and beverage industry as well as further research regarding business research in this field.